Mengenal Kare Kare Sebagai Warisan Kuliner Nagari Sulit Air Kabupaten Solok dalam Kegiatan KKN UNP 2025 - Alya Dwiyana Alwani Putri; Yosi Nasdiah; Alisya Putri Noviananda Rizwa; Inka Taruni Sastra; Yunanta Pramana Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines Kare Kare as a culinary heritage typical of Nagari Sulit Air, Solok Regency, West Sumatra. Using a qualitative approach with participatory observation techniques, interviews, and documentation, the study aims to document the history, manufacturing process, cultural values, and socio-economic role of Kare Kare. The results of the study indicate that Kare Kare has deep historical roots, passed down from generation to generation within the family. The manufacturing process reflects the local wisdom of the Minangkabau people, emphasizing the balance of ingredients and patience. Socio-economically, Kare Kare is a source of sustainable income and a marker of the collective identity of Nagari Sulit Air, especially for migrants. The main challenges in preserving Kare Kare are the lack of interest from the younger generation and changes in community consumption patterns. Conservation strategies include documentation of knowledge, production and marketing innovation, integration into local education, and development of culinary tourism through multi-party collaboration.